A dynamin-like protein, ADL1, is present in membranes as a high-molecular-mass complex in Arabidopsis thaliana. - Park, J M (1997)
Dynamin, a GTP-binding protein, is involved in endocytosis in animal cells. We found that a dynamin-like protein, ADL1, is present in multiple forms in Arabidopsis leaf tissue. Subcellular fractionation experiments, together with gel-filtration and nondenaturing-gel electrophoresis revealed that most of ADL1 is present as a high-molecular-mass complex of 400 to 600 kD in the membrane or pellet fraction, whereas ADL1 is present in the soluble fraction as a monomer. The subcellular distribution of ADL1 is affected by various agents such as Ca2+, cyclosporin A, GTP, and ATP. Ca2+ increases the amount of ADL1 present in the membrane fraction, whereas cyclosporin A inhibits the membrane association. Furthermore, Ca2+ and GTP change the migration pattern of ADL1 in nondenaturing polyacrylamide gels, indicating that these chemicals influence either the complex formation and/or the conformation of the ADL1 complex. Our results demonstrate that ADL1 has characteristics that are similar to Dynamin I, which is found in animal cells. Therefore, it is possible that ADL1 is also involved in biological processes that require vesicle formation.